HUBUNGAN NILAI DALAM PERKAWINAN DAN PEMAAFAN DENGAN KEHARMONISAN KELUARGA - Maria Nona Nancy; Yohanes Bagus Wismanto; Lita W. Hastuti (Universitas Katolik Soegijapranata, 2014)
This study examined the relationship between the value of marriage, forgiveness and family harmony. Major hypothesis in this research is there is positive relationship between the value of marriage, forgiveness and family harmony, while the minor hypothesis reads (1) there is positive relationship between the value of marriage and family harmony (2) there is positive relationship between forgiveness with family harmony. The method used in this research was quantitative research method. The research population were married couples living in the District of East Alok, District Alok and District West Alok, the city of Maumere, Sikka regency, amounting to 200 persons. The measuring instruments were a family harmony scale to measure family harmony, the value of marriage scales to measure the value of marriage and modification of Forgiveness Scale from Rye et al (2001) to measure forgiveness. The data were collected through the scales that were filled by married couples and then analyzed with regression analysis two predictors for major hypothesis and correlation bivariate techniques for minor hypothesis. The Results show that (1) there is a positive relationship between the value of marriage, forgiveness and family harmony, (2) there is a positive relationship between the value of marriage with family harmony, (3) there is a positive relationship between forgiveness with family harmony